BIOPESTICIDAL MANAGEMENT OF YELLOW STEM BORER (SCIRPOPHAGA INCERTULAS WALKER) IN RICE - S. BHUSHAN; RAJ PAL SINGH; RAVI SHANKER (The Bioscan, 2012)
An experiment was conducted during the year 2010 – 11 and 2011 – 12 to manage the stem borer in rice with biopesticides. The symptoms inflicted by stem borer in rice i.e. Dead Heart (DH) and White Ear Head (WEH) was found minimum (10.75 and 11.25%, resp.) in the plots managed by farmers with phorate 10 G. Although it did not differ significantly with the plots in which egg parasitoid, Trichogramma japonicum was released. T. japonicum exhibited 11.50 and 11.75% DH and WEH, respectively. The yield was also recorded maximum (31.7q/h) in the phorate treated plots followed by the plots in which egg parasitoid was released.